Gait phase recognition of lower limb exoskeleton system based on the integrated network model - Zhang, Zaifang; Wang, Zhaoyang; Lei, Han; Gu, Wenquan (Biomedical signal processing and control, 2022)
[Display omitted] •A new gait recognition method based on integrated network model is proposed for identifying four phases in the gait cycle, including heel strike, foot flat, heel off and swing phase.•This paper adopts sparse autoencoder into the model to extract key features of gait information and use bidirectional long short-term memory for learning more critical information from gait data.•The proposed integrated network model has more effective recognition results and better generalization performance for gait phase recognition of the lower limb exoskeleton system compared with other models. Exoskeleton robots have become an emerging technology in medical, industrial and military applications. Human gait phase recognition is the crucial technology for recognizing movement intention of the exoskeleton wearer and controlling the exoskeleton robot. As a new biometric recognition method, gait phase recognition also plays an important role in clinical disease diagnosis, rehabilitation training and other fields. This paper proposes an integrated network model SBLSTM that combines sparse autoencoder (SAE), bidirectional long short-term memory (BiLSTM) and deep neural network (DNN) aiming at gait phase recognition during human movement. The model can accurately identify four phases in the gait cycle, including heel strike (HS), foot flat (FF), heel off (HO) and swing phase (SW). Normalization and feature extraction of collected sensor signals are performed to enhance the accuracy of recognition during the gait identification process. The processed data are input into the SBLSTM model. The introduction of SAE into the model can extract key information from gait characteristics. BiLSTM is used to learn temporal patterns and periodic changes in gait data. DNN is adopted to identify gait phases and output classification results. Different algorithms such as DNN, LSTM and SBLSTM are applied to the gait phase detection of subjects. The experimental results show that the SBLSTM algorithm is effective in gait recognition. The accuracy and F-score are outperformed by other algorithms, which verifies the effectiveness of the SBLSTM in practice.